17α-estradiol acts through hypothalamic pro-opiomelanocortin expressing neurons to reduce feeding behavior - Steyn, Frederik J. (2018)
Weight loss is an effective intervention for diminishing disease burden in obese older adults. Pharmacological interventions that reduce food intake and thereby promote weight loss may offer effective strategies to reduce age-related disease. We previously reported that 17α-estradiol (17α-E2) administration elicits beneficial effects on metabolism and inflammation in old male mice. These observations were associated with reduced calorie intake. Here, we demonstrate that 17α-E2 acts through pro-opiomelanocortin (Pomc) expression in the arcuate nucleus (ARC) to reduce food intake and body mass in mouse models of obesity. These results confirm that 17α-E2 modulates appetite through selective interactions within hypothalamic anorexigenic pathways. Interestingly, some peripheral markers of metabolic homeostasis were also improved in animals with near complete loss of ARC Pomc transcription. This suggests that 17α-E2 might have central and peripheral actions that can beneficially affect metabolism cooperatively or independently.